Empowering Youth for Sustainable Cultural Tourism: A Case Study Tipang Village, Baktiraja District, Humbang Hasundutan Regency, Indonesia - Sormin, Amon; Sihombing, Hera (Jurnal Ilmu Pendidikan dan Humaniora, 2023)
This research delves into the dynamic interplay between youth and the development of cultural tourism in Tipang Village, located in the heart of Baktiraja District, Humbang Hasundutan Regency, Indonesia. Cultural tourism, a realm rich with tradition and history, is increasingly influenced by the innovative efforts of local youth. This study employs a mixed-methods approach, combining quantitative surveys, qualitative interviews, participant observations, and case study research to unravel the multifaceted role of youth in the cultural tourism landscape. The findings of this research uncover the transformative potential of youth as cultural stewards, their pivotal role in preserving and promoting cultural heritage, and their contribution to the economic growth of the village. Authentic cultural experiences emerge as a magnet for tourists, highlighting the importance of genuine encounters and intercultural exchange. The success of digital promotion, driven by youth, underscores the transformative potential of technology in cultural tourism. Moreover, the research emphasizes the commitment of Tipang Village to responsible tourism practices, promoting sustainability and the preservation of the cultural and natural environment. The role of youth as catalysts of change challenges traditional paradigms, illustrating their potential to shape the cultural tourism landscape positively. The implications of this research extend beyond Tipang Village, resonating with cultural tourism destinations worldwide. It offers valuable insights into the transformative power of youth, the allure of authenticity, the potential of technology, and the imperative of responsible tourism. This research celebrates the dynamic synergy between culture, youth, and tourism, concluding not as an endpoint but as a stepping stone to a future where tradition, empowerment, and global understanding unite to enrich the tapestry of cultural tourism.